Health and wealth in the North of Ireland: is there a ?social gradient? to health outcomes? - Borooah, Vani K. (Economic & Social Studies, 2007)
This paper investigates using data on 2,700 persons in the North of Ireland, whether there is a social gradient to health, both with respect to general health (self-assessed health status; long-term limiting illness; the existence of a health problem) and with respect to specific illnesses (asthma; arthritis; back pain; blood pressure problem; heart problem; mental illness). The evidence suggests that people who live in poor housing (for example, damp houses with inadequate heating) are more likely to be in bad health, in respect of both general health and specific ailments, than persons living in good housing. There is also evidence that persons without educational qualifications are more likely to be in bad health than persons who have educational qualifications. Lastly, the results point to the fact that higher levels of household income are associated with better health outcomes. If one defines the ?social gradient? in terms of these three factors ? housing quality, education qualifications, and income level ? then the results suggest that people?s health outcomes depend upon their position on the social ladder.
Paper presented at the Twentieth Annual Conference of the Irish Economic Association, Bunclody, Co. Wexford 2006
Keywords: Health status; Social gradient; Northern Ireland; Health problems